2019
DOI: 10.1177/1529100619832930
|View full text |Cite|
|
Sign up to set email alerts
|

Emotional Expressions Reconsidered: Challenges to Inferring Emotion From Human Facial Movements

Abstract: It is commonly assumed that a person’s emotional state can be readily inferred from his or her facial movements, typically called emotional expressions or facial expressions. This assumption influences legal judgments, policy decisions, national security protocols, and educational practices; guides the diagnosis and treatment of psychiatric illness, as well as the development of commercial applications; and pervades everyday social interactions as well as research in other scientific fields such as artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
961
2
21

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,138 publications
(1,024 citation statements)
references
References 352 publications
(559 reference statements)
40
961
2
21
Order By: Relevance
“…That is, there are six facial configurations that, when observed in isolation, are most of the time interpreted to communicate these emotion categories (6). Indeed, many studies have been completed that confirm this view, although more recent studies have identified a much larger set of expressions, including compound emotions such as happily disgusted as well as other affective signals (2,7). But context remains essential to correctly interpret facial expressions, as demonstrated in the examples in Figs.…”
Section: Facial Expressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, there are six facial configurations that, when observed in isolation, are most of the time interpreted to communicate these emotion categories (6). Indeed, many studies have been completed that confirm this view, although more recent studies have identified a much larger set of expressions, including compound emotions such as happily disgusted as well as other affective signals (2,7). But context remains essential to correctly interpret facial expressions, as demonstrated in the examples in Figs.…”
Section: Facial Expressionsmentioning
confidence: 99%
“…1, most people identify a female expressing sadness on the left and an angry male on the right. But while identity and other attributes are recognized quite accurately (1), affect is not (2). To see this, look at the images in Fig.…”
mentioning
confidence: 99%
“…Moreover, Gale and Martyn (1996) suggest that pacifiers could influence not only babies' emotional skills but their general intelligence. By 3 years of age children begin to show reliability in facial expressions, associate them with specific meanings and contexts (Feldman Barrett et al, 2019;Ruba et al, 2019), and be aware of display rules (Cole, 1986). Even beyond these early developmental periods, people's emotion concepts are affected by the input from their environment (Levari et al, 2018).…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…Similarly, in a conceptually analogous manipulation of transitive affect, Dezecache et al (2013) found that explicit identifications of positive faces were not above chance, while ZM activity increased for positive faces (Dezecache et al, 2013). Furthermore, results from two experiments conducted by Fridlund (1991) support the claim that implicit facial expressions may be erratically associated with explicit subjective reports of emotional experiencefor a detailed review, see Barrett et al (2019). We believe these results are puzzling because subjective measures either collected in a single bipolar scale (Deng and Hu, 2018) or as discrete identifications (Dezecache et al, 2013) do not provide enough information to determine the amount of subjective contagion experienced by participants.…”
Section: Introductionmentioning
confidence: 74%